CORRELATION BETWEEN SOCIOECONOMIC STATUS OF PARENTS AND ORTHODONTIC TREATMENT NEEDS IN THE STUDENTS OF SMAN 10 BANJARMASIN - Restika Hidayati; Diana Wibowo; Riky Hamdani (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Malocclusion is defined as an occlusion deviation from the functionally normal conditions. Malocclusion in adolescents results in speech difficulties, masticatory disorders and social problems due to disturbed facial appearance. The purpose of orthodontic treatment needs is to overcome joint problems in the jaw and follow the lifestyle, one of which is aesthetic needs. The high rate of orthodontic treatment is due to the different mindset of adolescents based on their parents’ education category and economic status. Objective: To analyze correlation between  socioeconomic status of parents and orthodontic treatment needs in the students of SMA Negeri 10 Banjarmasin. Method: This research used analytic observational method with a cross-sectional approach. The samples were 80 students of SMAN 10 Banjarmasin. Data collection was using a socioeconomic status questionnaire, while the malocclusion was using IOTN-AC. Results: The orthodontic IOTN-AC measurement results in SMA Negeri 10 Banjarmasin were 36 people (45%) with a Grade C index category which is indicative of treatment. The socioeconomic status of parents is in the middle to lower income level with the highest frequency of 69 people (86.3%). Spearman correlation test results that the significance level of parents’ education with orthodontic treatment needs was 0,000 (p <0.05) with the correlation coefficient of 0.469, and parental employment status of 0.003   (p <0.05) with the correlation coefficient of 0.326. The significance value of the income level was 0,000 (p <0.05) and the correlation coefficient was 0.540. Conclusion: There is a significant correlation between socioeconomic status of parents and orthodontic treatment needs in the students of SMAN 10 Banjarmasin.